The Influence of Government Expenditure on the Human Development Index in NTT Province - Banase, Marianus Antonius Deo Datus; Purwono, Rudi (Jurnal Ilmu Ekonomi Terapan, 2024)
Researchers analyzed government spending on health, education, and infrastructure in influencing the human development index in NTT Province. The research data is panel data in 22 districts/cities, namely health, education, and infrastructure expenditure data for 2010-2022. Panel data regression analysis used the pooled least square method to analyze government spending. The results found that government spending on health, education, and infrastructure together (simultaneously) significantly influenced the human development index in districts/cities in NTT province. Another analysis found that government spending on health and education partially influenced the human development index significantly in the districts/municipalities of the NTT province. However, spending on infrastructure partially had no significant effect on the human development index in the districts/municipalities of the NTT province. The implications of the research are improvements in health, education, and infrastructure that can increase development.